Perfil emocional e de consumo: influência de diferentes estilos de cerveja no comportamento de consumidores e não consumidores da região sul do país - Steinbach, Juliana (2022)
Beer is the most consumed alcoholic beverage in the world, so there is great scientific interest about this product and its correlates, with emphasis on the artisanal segment. The craft style is differentiated in terms of process, sensory characteristics and also the consumer, who has greater involvement with the product, which leads to an interest in the emotional responses evoked by the product. From the above, the present study sought to establish the profile of the consumer and their emotional relationship with craft beer compared to the traditional version, and also to understand the non-consumers of the product. Data were obtained through an online questionnaire, with 550 consumers and non-consumers in the Southern Region of Brazil. Craft-style consumers have a higher level of education and income than traditional beer consumers, as these parameters increase the chance of consuming traditional beer drops by 27% and 23% respectively. There was no significant difference between genders for the chance of consuming beers of different styles. Consumer attitudes and relevant attributes in beer choice have a significant difference between the style consumed and the consumer's gender. Craft consumers show a preference for more bitter, exotic beers, with a strong and full-bodied flavor, seeking high quality and authenticity, taking into account the local economy, the place of origin of the beer, safety and, above all, the flavor at the time of choice. Traditional beer drinkers, on the other hand, are looking for familiar, easy-drinking beers, given their ease of finding and price. detain the convenience and availability of the product at the time of choice. The high price, together with the stronger and sometimes exotic flavor, are the main reasons for this group to consume little or even not consume craft beer. Non-consumers of any style of beer also report the taste of the product as a barrier to consumption, and in general they are not interested in consuming non-alcoholic beer, on the other hand, they show interest in the consumption of wine as an alternative beverage. Emotional associations to products are generally positive, especially in relation to craft beer, with the exception of the group of non-consumers who have a negative relationship with traditional beer. This information can help the brewing segment to make adjustments to its products and ways to relate to the consumer to maximize the consumption experience.